2014
DOI: 10.12674/ptk.2014.21.3.045
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Elderly Fallers and Elderly Non-Fallers: Balancing Ability, Depression, and Quality of Life

Abstract: 1)Fall is one of the most intimidating health conditions in elders. Comprehensive assessment is necessary to understand the individual and environmental aspects of the falls such as balancing abilities, depression, and quality of life. The purpose of this study was to compare the balancing ability, depression, and quality of life between elderly fallers and elderly non-fallers. Thirty-two community-dwelling elders (fifteen males and seventeen females between 65 and 83 years old), who have experienced fall on w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
1
8
1
Order By: Relevance
“…Another study of older adults in the community also found that women were more likely to fall than men, and that those participating in economic activity were more likely to fall than those who were not 15 ) , but the differences were not significant. The results of other studies of older adults and people without a history of stroke contradict those of the present study 14 , 21 , 22 ) .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Another study of older adults in the community also found that women were more likely to fall than men, and that those participating in economic activity were more likely to fall than those who were not 15 ) , but the differences were not significant. The results of other studies of older adults and people without a history of stroke contradict those of the present study 14 , 21 , 22 ) .…”
Section: Discussioncontrasting
confidence: 99%
“…The HRQOL results of fallers and non-fallers were similar to those of previous studies 14 , 21 ) . In particular, the study of Choo et al 14 ) , which used a short form-8 health survey to assess various subdomains of HRQOL, found there were significant differences in physical function, bodily pain, social function, role functioning-emotional, and mental health.…”
Section: Discussionsupporting
confidence: 88%
“…To determine the quality of life index, we used the Korean version of the WHOQOL‐BREF developed by Min, Lee, Kim, Suh, and Kim (). This is a self‐administered questionnaire to assess the quality of life (Jeon, Jeon, Yi, & Cynn, ). The reliability of this instrument was Cronbach's α = 0.92.…”
Section: Methodsmentioning
confidence: 99%
“…It consists of a total of 26 items, and each item is rated on a Likert‐type 4‐point scale with the score range of 1–4 points. The total scores range from 26 to 130 points, and higher scores indicate higher levels of the quality of life (Jeon et al, ). The subdomains of WHOQOL‐BREF are the overall domain, physical domain, psychological domain, social domain, and environment domain, and the items reverse scored by recoding were Items 3, 4, and 26, and they are negative statement items (Kim, Lee, & Park, ).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the reduction of skeletal muscle due to aging limits the activities of daily living, task performance and leisure activities, resulting in decreased motility, increased risk of falling, increased functional dependency, and lowered quality of life [2]. Approximately one-third of the elderly experience falls each year, and as the age increases, the fall rate increases [3,4]. Falls are affected by gender, cohabitation, presence of illness, emotional depression, exercise, and smoking [5], and it reduces self-confidence in activity and balance performance for daily life [6].…”
Section: Introductionmentioning
confidence: 99%